History of international relations development among Russia and African countries in the beginning of the XXI century - M. M. Mahamat (Вестник университета)
Dynamics of economic relations development among Russia and African countries in the beginning of the 21st century has been analyzed. At that time there was the economic relations strengthening among Russia and African countries, which was caused by several factors: 1) the interest of Russian companies in the resource potential of Africa; 2) the support of the Government of the Russian Federation for the export of goods and services to African countries; 3) the growth of trade among Russia and African countries; 4) the increase in investments of Russian companies in African countries. At the beginning of the 21st century, Russia and African countries strengthened their cooperation in the economic sphere. It had a positive impact on both sides, contributing to African countries development and Russian companies’ expansion in this market, and strengthening regional stability. Acting on the dual front of bilateral diplomacy and multilateralism, Russia, through the BRICS forum, must ﬁnd its place on the continent. Central Africa has strengthened its economic relations with China, India, and Brazil while developing its own activities on the continent.